Fostering positive attitude in probability learning using graphing calculator - Tan, Choo Kim; Bava Harji, Madhubala; Lau, Siong Hoe (Elsevier, 2011)
Although a plethora of research evidence highlights positive and significant outcomes of the incorporation of the Graphing Calculator (GC) in mathematics education, its use in the teaching and learning process appears to be limited. The obvious need to revisit the teaching and learning of Probability has resulted in this study, i.e. to incorporate GC in the teaching and learning of Probability, specifically on the issue of attitudes towards learning probability. The objective is to examine the effectiveness of GC interactive learning, particularly on students' attitudes towards Probability. A total of 65 foundation students participated in this study; 32 students in the experimental group and 33 in the control group. The teaching approaches varied between the groups. While the experimental group experienced the GC approach, the control group encountered the conventional teaching approach of chalk and talk. Students' attitude towards learning probability was assessed using the Probability Attitude Inventory (PAI), was administered prior to and after the study. The results show significantly difference in the improved attitude towards Probability between the groups, particularly in terms of usefulness of Probability, interest in Probability and self-concept in Probability. This study provides evidence that learning Probability with GCs benefits students.